Analysis of an Off-grid PV System for Disaster Mitigation Scheme in Remote Areas - Pinto Anugrah; Putty Yunesti; Guna Bangun Persada (Andalas Journal of Electrical and Electronic Engineering Technology, 2021)
The main objective of this paper is to present the techno-economic analysis of an off-grid Photovoltaic system, which prepared to support disaster mitigation scheme in remote areas. As a case study, a regency in Mentawai Island, Sumatera Barat is chosen to represent a remote area in a disaster-prone location. The proposed system capacity is 20 kWp PV system as a single electricity source for medical facility in the island. As a tool in this study, RETScreen software was used to analyze the technical, environmental, and economical feasibility analysis. As a base case scenario, the medical facility was supported by a diesel-fueled generator and the PV system can deliver 10.14 MWh of electricity to load annually. Net annual GHG emission reduction of the system is 19.4 ton of CO2 equivalent. With the total initial cost for the whole PV system at USD 41,380, RETScreen simulation result showed that the equity payback of the project is 6.0 years with IRR of 11.9% hence the project is financially viable.